Do handball throws always exhibit a proximal-to-distal segmental sequence? - Fradet, L.; Botcazou, M.; Durocher, C.; Cretual, A.; Multon, F.; Prioux, J.; Delamarche, P. (Journal of Sports Sciences, 2004)
Previous studies on overarm throwing have described a proximal-to-distal segmental sequence. The proximal segments reached their maximal linear velocities before the distal ones. In handball, no study has demonstrated this sequence from the upper torso to the wrist, although a recent study did present a different organization. The aim of this study was to analyse the throwing arm segmental organization during handball throwing. We found that the maximal linear velocity of the shoulder occurred after the maximal linear velocity of the elbow. Moreover, the maximal angular velocity of the upper torso occurred later than that of the elbow. Hence, contrary to other disciplines, the rotation of the upper torso was not suddenly stopped just after the forward arm motion was initiated. These results may apply to handball in general or be specific to the population of handball players studied. It may be advisable in future studies to include international players.